The Anxiety Level of Pregnant Women Who Will Undergo Sectio Caesarea Operation at Harapan Hospital Pematang Siantar - Ance Siallagan; Rotua Elvina Pakpahan; Murni Sari Dewi Simanullang; Rosdiyanti Sinaga (Sean Institute, 2023)
The surgical procedure is a potential or actual stressor or threat that causes anxiety in the patient. The causes of preoperative anxiety are related to surgical procedures and anesthesia which cause an increase in heart rate, blood pressure, respiratory rate, and reduce the patient's energy level. Anxiety in pregnant women who will undergo sectio caesarea surgery will result in an increase in the mother's vital signs and stress on the fetus. The purpose of this study was to identify the level of anxiety in preoperative sectio caesarea patients at Harapan Pematang Siantar Hospital. This study uses a descriptive design on 66 pregnant women who will give birth by section caesarea through total sampling technique. Data collection was carried out in April 2023 with the Amsterdam Preoperative anxiety and Information Scale questionnaire. The results showed that the respondents' anxiety levels were in the moderate (65.2%) and mild (3.0%) categories. Preoperative anxiety is strongly influenced by the understanding of information and the readiness of the mother physically and mentally. Mothers who will give birth by caesarean section should be trained in relaxation techniques, given clear information about the procedure and effects of anesthesia, accompanied by their husbands or family members so that they have internal motivation that can reduce anxiety levels so that the operation goes well.